Studi Fenomenologi: Pengalaman Remaja Perempuan Menjalankan Peran Sebagai Ibu - Fitri Fujiana (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2020)
Carrying out the role of a mother is not easy, especially for a teenage girl. Pregnant, giving birth and caring for a baby has its challenges for adolescent girls. The purpose of this study is to explore deeply the experiences of adolescent girls in carrying out their roles as mothers. This research is qualitative research with a phenomenological approach. Data collection was carried out by using in-depth interviews with seven informants. Data analysis was performed using the Moustakas content analysis thematic approach. This study produced three broad themes. The first theme is that young women do not give exclusive breastfeeding to their babies. The second theme is that adolescent girls cannot do basic baby care. The third theme is teenage girls not knowing the process of pregnancy. The young age and growth and development are not optimal making adolescent girls have difficulty in carrying out the role of motherhood. Lack of knowledge and experience causes adolescent girls are not optimal in providing the best for their children. Nurses especially maternity nurses can provide health education to adolescent girls in caring for newborns. Nurses can also educate adolescent girls to prepare themselves before deciding to become a mother.Keywords: Teenage mother; Maternity nurse; Newborn baby; Exclusive breastfeeding